Formation Mechanism and Microphysics Characteristics of Heavy Rainfall Caused by Northward-moving Typhoons - Li Xin; Zhang Lu (应用气象学报, 2022)
Local torrential rain and short-term heavy rainfall of small spatial-temporal scale are caused by northward-moving Typhoon Lekima (1909) and Typhoon Bavi (2008) in Qingdao area, with the maximum hourly rainfall of 60.3 mm·h-1 and 130.1 mm·h-1, respectively, while the prediction performance of numerical weather prediction model is very poor. Using NCEP FNL analysis data, raindrop spectrum and polarimetric radar data, the microphysics characteristics of the heavy rainfall are analyzed. The rainfall mainly occurs in a narrow belt region extending northwestward from the coastal mountainous area. The warm and humid air is transported by the southeast wind strengthens the instability. Convective cells are constantly triggered by topography or boundary layer front, and then move northwestward and form linear multicell storms under strong wind condition, or merges into local strong storms when the wind is weak. Both can cause local heavy rainfall. The mass weighted average diameter (Dm) and logarithmic normalized intercept (lgNw) are 1.89 mm and 3.86, respectively, which are between tropical marine-time and continental convective precipitation, indicating a larger mean diameter and lower number concentration compared to the typhoon rainfall in East China and South China. The μ-Λ slope is also significantly different, indicating the dominant microphysical processes are different. With the increase of rainfall intensity, the proportion of small particles below 1 mm decreases significantly, and the proportion of medium-large particles increases, indicating significant collision-coalescence process. Particles with 1-4 mm diameters contribute more than 90% to short-term heavy rainfall. When hourly rainfall is more than 50 mm·h-1, the proportion of small particles increases and particles with 2-3 mm diameter changes little, indicating that breakup and collision-coalescence process reaches equilibrium. Aggregate process and dry snow is dominant above -20℃ level and grapuel produced by riming process is dominant between -10℃ and 0℃ level. With the decrease of height, the values of ZH, ZDR and KDP increase, and raindrops change from light rain to heavy rain particles. At the same time, the liquid water content is significantly greater than ice water content, indicating that the collision-coalescence and accretion process play a critical role in the formation of heavy rainfall. Riming process also plays an important role in extreme heavy rainfall, during which its height can reach near -20℃ layer. The positive feedback of latent heat release leads to the strengthening of convective activity, resulting in more graupel particles and greater ice water content. The melting of graupel directly increases the rainfall. On the other hand, it produces big droplets, which enhance the warm-rain processes and leads to the increase of rainfall intensity.